Ultrasound of Shoulder Joint Another Diagnostic Modality - Rashid, Sabrina Q (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Shoulder is an important joint, in fact the most important joint which needs an ultrasound evaluation for not only the diagnosis of the pathology but also its follow-up during treatment. Ultrasound is also an important modality needed for the treatment of joint pathologies like fluid aspiration or intra-articular injections. It is gaining more importance now, due to availability of the high-end digital ultrasound machines with their superior image quality, using high frequency ultrasound probes. So that now even very superficial and very thin muscle fibers, tendons and ligaments can be very well visualized. Diagnosis of small tears, inflammations and small fluid collections can now be made easily. In this paper there is technique for the ultrasound of the shoulder joint with a discussion and review of its importance. J Bangladesh Coll Phys Surg 2023; 41: 82-88